Método de apoio à inovação do produto de software em uso utilizando mineração de opinião de usuários na web - Frank Mendes Nobre (2011)
A method can be understood as a way or a rational process to reach the solution of a determined problem. This work propose a method to verify and evaluate the user\\\'s opinion about the software product in use in Web. It discusses the potential of this method to support on the search problem related to inovation - incremental or radical - of the software product when analysing these user\\\'s opinion. This method is based in a study that integrates software engineering areas, mainly : software quality, evaluation and maintenance; Inovation and software inovation; and web data mining. This method was evaluated using a case study where have been used the Windows Vista software product and opinions presented in webpages from the Clube do Hardware forum. The results reached in this case study were satisfactory and they indicated user\\\'s opinions that can lead to a quality improvement and, thus, to inovate the software product being evaluated, according analysis and management decision by the maintainer.